EFEKTIVITAS PERMAINAN BINGO DALAM PEMBELAJARAN PROGRAM APLIKASI KELAS VII SMP NEGERI 25 PURWOREJO - Yulaekha, Novita Rizka; Sudana, I Made; Arief, Ulfah Mediaty (Edu Komputika Journal, 2017)
Based on observation at 25 junior high school Purworejo are gotten data that learning process TIK still using lecture method and using media still less. That is effect low studying result, we can looking by seven classs odd final examination result with mean classical studying completeness as 43,85%. This research purpose to know are there increasing student study result and to know are student study result with bingo learning media effective learning process. Research method is experiment with quasi experiment design. Sampling in quasi experiment use non random sampling technique that is purposive sampling. Quasi experiment design form is Nonequivalent control group design. This research result show that mean pretest experiment class as 67,42 whereas mean posttest experiment class as 83,28. Mean pretest control class as 66,48 whereas mean posttest control class as 76,09. Based on t-test analysis, there are increasing student study result with thitung = 2,77. Based on gain analysis, increasing study result experiment class in medium category that is 0,49 whereas increasing study result control class in low category that is 0,28 so student study result with bingo learning media effective learning process.